2012
DOI: 10.1100/2012/759604
|View full text |Cite
|
Sign up to set email alerts
|

Study of Saiga Horn Using High-Performance Liquid Chromatography with Mass Spectrometry

Abstract: The saiga horns have been investigated the using of modern analytic methods. High-performance liquid chromatography (HPLC) with mass-spectrometric (MS and MS/MS) detection and polyacrylamide gel electrophoresis (PAGE) were used. It could be concluded that basic proteins of the saiga horns are keratins and collagen. The basic representation protein in all samples is keratin type I microfibrillar (from sheep), keratin type II microfibrillar (from sheep), collagen type I (α 1) (from bovine) and collagen type I (α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…The results of this study also confirmed that collagens (α1, type I and α2, type I) and keratins (type I cuticular, type I microfibrillar, type I cytoskeletal, type II cuticular, type II microfibrillar and type II cytoskeletal) are the main constituents of Saiga horn as we previously reported in another study, which was performed on an ion-trap mass spectrometer [15]. In addition to that, we have now been able to identify two other proteins -collagen α1, type III and macrophage migration inhibitory factor.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study also confirmed that collagens (α1, type I and α2, type I) and keratins (type I cuticular, type I microfibrillar, type I cytoskeletal, type II cuticular, type II microfibrillar and type II cytoskeletal) are the main constituents of Saiga horn as we previously reported in another study, which was performed on an ion-trap mass spectrometer [15]. In addition to that, we have now been able to identify two other proteins -collagen α1, type III and macrophage migration inhibitory factor.…”
Section: Discussionsupporting
confidence: 90%
“…LC–MS/MS analysis of Saiga horn extracts confirmed that the main components are keratin type I microfibrillar, keratin type II microfibrillar and collagen type I (α1 and α2 chains) .…”
Section: Introductionmentioning
confidence: 86%
“…In horn (but not baleen and porcupine), cytoskeletal keratins are detected but few keratin‐associated proteins are (in wool up to 13 cytoskeletal keratins, and 36 KAPs can be found). Cytoskeletal keratins had also been detected in the horn of Saiga . Separation by two‐dimensional (2D) gels conducted at AgResearch on rhinoceros horn showed a lower abundance of proteins in the KAPs area compared to wool fibres (unpublished data).…”
Section: Resultsmentioning
confidence: 94%
“…However, with increasing human population and demand, illegal hunting has led to drastic reductions in rhinoceros and Saiga antelope populations in recent decades3. Even though five species of rhinoceros are listed as endangered according to the International Union for Conservation of Nature (IUCN) and Appendix I of the Convention on International Trade in Endangered Species (CITES)45, the law seems to have done little to save these species, and the African rhinoceros population has declined from 65,000 to less than 3500 over the last 40 years.…”
mentioning
confidence: 99%
“…Similarly, a place on Appendix II of the CITES list for the Saiga antelope failed to protect this species, and the population has fallen drastically from 1 million in the 1980s to only 25,000 in 2000. This species was placed on the endangered species list in 200134.…”
mentioning
confidence: 99%